Detailed stellar and gaseous kinematics of M31. Issue Volume 10:Issue S309(2014) (9th February 2015) - Opitsch, Michael; Fabricius, Maximilian; Saglia, Roberto; Bender, Ralf; Williams, Michael
Abstract: We have collected optical integral field spectroscopic data for M31 with the spectrograph VIRUS-W that result in kinematic maps of unprecedented detail. These reveal the presence of two kinematically distinct gas components.